L’ancien et le nouveau - Faribault, Bernard (Assurances)

(untitled) (HEC Montréal, 1992)
Over the past sixteen years, various aspects of the articles of the Civil Code of Québec dealing with insurance, have been scrutinized by our Courts. Me Faribault has selected a few cases which, for better or for worse, seem to have caught the eye of our lawmakers and prompted other changes in this field, which came into effect when the new Civil Code of Quebec was enacted fast December.